Microcontroller and Android Based Automatic Identification System for Inland Waterway - Rokonuzzaman M.; Shakib N.; Shakil M.R.; Islam K.; Hasan Khondoker M.R.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Android (operating system); Automation; Controllers; Cost effectiveness; Global positioning system; Microcontrollers; Android applications; Android virtual device; Application systems; Automatic identification system; Google maps; IS costs; Microcontroller; Microcontroller-based; Virtual devices; Ships